Mutations specific to the Rac-GEF domain of TRIO cause intellectual disability and microcephaly. Issue 11 (14th July 2016) - Pengelly, Reuben J; Greville-Heygate, Stephanie; Schmidt, Susanne; Seaby, Eleanor G; Jabalameli, M Reza; Mehta, Sarju G; Parker, Michael J; Goudie, David; Fagotto-Kaufmann, Christine; Mercer, Catherine; ,; Debant, Anne; et al.
Abstract : Background: Neurodevelopmental disorders have challenged clinical genetics for decades, with over 700 genes implicated and many whose function remains unknown. The application of whole-exome sequencing is proving pivotal in closing the genotype/phenotype gap through the discovery of new genes and variants that help to unravel the pathogenic mechanisms driving neuropathogenesis. One such discovery includes TRIO, a gene recently implicated in neurodevelopmental delay. Trio is a Dbl family guanine nucleotide exchange factor (GEF) and a major regulator of neuronal development, controlling actin cytoskeleton dynamics by activating the GTPase Rac1. Methods: Whole-exome sequencing was undertaken on a family presenting with global developmental delay, microcephaly and mild dysmorphism. Father/daughter exome analysis was performed, followed by confirmatory Sanger sequencing and segregation analysis on four individuals. Three further patients were recruited through the deciphering developmental disorders (DDD) study. Functional studies were undertaken using patient-specific Trio protein mutations. Results: We identified a frameshift deletion in TRIO that segregated autosomal dominantly. By scrutinising data from DDD, we further identified three unrelated children with a similar phenotype who harboured de novo missense mutations in TRIO . Biochemical studies demonstrated that in three out of four families, the Trio mutations led to a markedly reduced Rac1 activation. Conclusions: We describe an inherited global developmental delay phenotype associated with a frameshift deletion in TRIO . Additionally, we identify pathogenic de novo missense mutations in TRIO associated with the same consistent phenotype, intellectual disability, microcephaly and dysmorphism with striking digital features. We further functionally validate the importance of the GEF domain in Trio protein function. Our study demonstrates how genomic technologies are yet again proving prolific in diagnosing and advancing the understanding of neurodevelopmental disorders.